Pengembangan Ruang Belajar Virtual Geography Crops Untuk Meningkatkan Kemampuan Berfikir Spasial Peserta Didik SMA - Azzukhruf, Nadhifan Fawwazian; Suharto, Yusuf (Cetta: Jurnal Ilmu Pendidikan, 2025)
Virtual learning spaces that are contextual and interactive have become a primary need in geography education, particularly in en hancing students’ spatial thinking skills. This study focuses on developing a virtual reality-based learning medium, designed as a digital learning space to facilitate the study of plantation resource potential. The purpose of this research is to develop and evaluate the effectiveness of learning medium in improving students’ spatial thinking abilities. The research method employed is the ADDIE model, consisting of five stages (Analysis, Design, Development, Implementation, Evaluation). Data collection was conducted through direct observation. For the analysis of the collected data, the researcher used descriptive statistical analysis techniques. The results indicate that the developed learning medium falls into the category of highly valid. Expert evaluations showed that media expert rated the learning medium at 84.70%, while material expert gave a score of 83.75%. Furthermore, student respondents rated the medium at 84.62%, and teacher respondents provided a score of 94.11%. Based on these four evaluation result, the medium is categorized as highly valid and suitable for use in the learning process. Additionally, the medium has a positive impact on students’ spatial thinking abilities, as evidence by an increase in average student scores at each stage, with a 37.38% improvement in stage 1 and a 7.63% improvement in stage 2. Based on these findings, it can be concluded that the developed medium is highly appropriate for application in learning activities and has a positive effect on enhancing students’ spatial thinking skills.